Salmonella in the tropical household environment – Everyday, everywhere. Issue 6 (December 2015) - Williams, Shellee; Patel, Mahomed; Markey, Peter; Muller, Rosanne; Benedict, Suresh; Ross, Ian; Heuzenroeder, Michael; Davos, Dianne; Cameron, Scott; Krause, Vicki
Summary: Objectives: To determine the prevalence of Salmonella in the environment of case and control houses, and compare serovars isolated from cases and their houses. Methods: From 2005 to 2008, we tested samples from houses of 0–4 year old cases and community controls in Darwin and Palmerston for Salmonella . Case isolates were compared with environmental isolates. S . Ball and S . Urbana isolates were compared using Multiple Amplification of Phage Locus Typing (MAPLT) and Multiple-Locus Variable number of tandem repeat Analysis (MLVA). Results: Salmonella were found in 47/65 (72%) case houses and 18/29 (62%) control houses; these proportions were not significantly different. In 21/47 (45%) houses, case and environmental isolates (from animal faeces, soil and vacuums) were indistinguishable. Multiple serovars were isolated from 20 (31%) case and 6 (21%) control houses. All but one environmental isolate are known human pathogens in the Northern Territory (NT). Each of the four pairs of S. Ball and S. Urbana were indistinguishable. Conclusions: Animal faeces were the most likely source of salmonellosis in cases. The similar prevalence of house isolates suggests that Salmonella is ubiquitous in this environment. The distinction of S. Ball and S. Urbana subtypes enabled linkage of human illness to environmental exposure. Environmental contamination with Salmonella is an important source of sporadic infection in children in the tropics. Highlights: Australia's Northern Territory has the highest notification rate of salmonellosis. Frogs and lizards frequent tropical households and harbour Salmonella. We found a similar prevalence of case and control house Salmonella isolates. Isolate subtyping enabled linkage of human illness to environmental exposure. Animal faeces were the most likely source of childhood salmonellosis in cases.